Challenges experienced by Portuguese professionals in humanitude care for institutionalized elderly people during the pandemic - Kátia Lilian Sedrez Celich; Rosa Cândida Carvalho Pereira de Melo; Mara Ambrosina de Oliveira Vargas; Francielly Zilli; Liliana Vanessa Lúcio Henriques; Jeane Barros de Souza (Revista da Escola de Enfermagem da USP, 2022)
Abstract Objective: To understand the challenges experienced by Portuguese workers in humanitude care for institutionalized elderly people during the pandemic. Method: This is a qualitative study, supported by reflections on the Humanitude Care Methodology, carried out with workers from different areas in a nursing home for elderly people in Portugal. Data collection took place between September and October 2020, from individual and online interviews. The categorization proposed by Bardin was adopted as the analysis technique. Results: Three categories emerged: (1) self-protection and of the other with the subcategories fear of being contaminated and fear of contaminating the elderly; (2) maintenance of affective relationships, broken down into the subcategories absence of family members in the nursing home and personal protective equipment as a barrier to communication and approximation; and (3) confinement of the elderly who attended the Day Center, with the subcategories lack of family support/loneliness and change in the elderly’s routine. Conclusion: The main challenges experienced by Portuguese workers are related to the necessary changes in the performance of care practices due to the use of personal protection that was not used before, limitations in affective relationships, and restrictions in interaction spaces.